Party Identification as a Female Voting Determinant in Karak, Khyber Pakhtunkhwa: A Case Study of 2018 General Elections - Rifat Nazir; Ashfaq U. Rehman; Muneeb U. Rehman, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This article investigates the electoral behaviour of females in district Karak, Khyber Pakhtunkhwa, Pakistan, and the case study is the 2018 general elections. This study tests the theory of party identification while using a quantitative research method. The data is collected through questionnaires from the field. Four hundred respondents have been selected out of the total of 178,504 female registered voters for elections of district Karak through Taro Yamane's Formula. The researchers have utilised a stratified sampling technique to gather reliable data of proportionate sampling figures from the female registered voters for the general election 2018 in NA-34 in district Karak. Therefore, the proportional allocation method of sampling, i.e., n1=N1/Ni x ni, is used to select the number of respondents from each tehsil according to the sample size. The study evaluates the role of party identification in describing female voting behaviour. The study's findings show that party affiliation is a critical determinant of NA-34 in the 2018 general elections in Karak, Pakistan.